2016
DOI: 10.1073/pnas.1520560113
|View full text |Cite
|
Sign up to set email alerts
|

Integrated in vivo and in vitro nascent chain profiling reveals widespread translational pausing

Abstract: Although the importance of the nonuniform progression of elongation in translation is well recognized, there have been few attempts to explore this process by directly profiling nascent polypeptides, the relevant intermediates of translation. Such approaches will be essential to complement other approaches, including ribosome profiling, which is extremely powerful but indirect with respect to the actual translation processes. Here, we use the nascent polypeptide's chemical trait of having a covalently attached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 64 publications
2
64
0
Order By: Relevance
“…More broadly, increasing the expression of low abundance tRNAs (which often correlate with rare codons) increased the aggregation of many E. coli cytoplasmic proteins [36], suggesting that slower translation might lead to higher folding yields for a variety of proteins. Consistent with this hypothesis, a correlation has been observed between translational pauses in E. coli coding sequences and protein solubility [37]…”
Section: Effects Of Synonymous Codon Substitutions On Protein Foldingmentioning
confidence: 74%
“…More broadly, increasing the expression of low abundance tRNAs (which often correlate with rare codons) increased the aggregation of many E. coli cytoplasmic proteins [36], suggesting that slower translation might lead to higher folding yields for a variety of proteins. Consistent with this hypothesis, a correlation has been observed between translational pauses in E. coli coding sequences and protein solubility [37]…”
Section: Effects Of Synonymous Codon Substitutions On Protein Foldingmentioning
confidence: 74%
“…Indeed, the existence of SD-mediated pauses has not been confirmed using several other experimental methods (Borg and Ehrenberg 2015; Chadani et al 2016; Mohammad et al 2016). Thus, remains unclear what role, if any, SD sequences within protein coding genes have in modulating translation speed (Figure 1B).…”
mentioning
confidence: 94%
“…Polypeptides of less than full length do not necessarily represent nascent states of the proteins because they can arise for various reasons, including proteolysis. The fact that nascent polypeptides carry a tRNA at the growing end can be exploited for the valid detection of cellular nascent polypeptides, by either two-dimensional (before and after tRNA removal; see above section A TCA Biologist; Figure 2) or one-dimensional (searching for RNase-sensitive materials) electrophoresis (16,44). Using such a method, I collaborated with Tatsuhiko Abo and Yuhei Chadani to show that E. coli cells can produce significant fractions of futile translation products in the forms of polypeptidyl-tRNAs, although these are normally prevented from appearing by the ribosome-rescuing pathways (44).…”
Section: Nascentomementioning
confidence: 99%
“…Previously, such systems for quality control of translation complexes had only been studied using model nonstop constructs. Yuhei later joined my lab and profiled nascent chains of individually expressed E. coli genes; he found that translational pausing, occurring in different modes, is unexpectedly widespread (16). Although the ribosome-profiling technique has higher throughput and resolution, it is important to detect and characterize translational pausing more directly using methods such as ours.…”
Section: Nascentomementioning
confidence: 99%